PENGARUH MEDIA SOSIAL TERHADAP ELEKTABILITAS BAKAL CALON PRESIDEN DAN WAKIL PRESIDEN - Najwa El-Khoir Hasibuan; Ulfah Fadilah Sidabalok; Rahmat Afandi; Marzuki Manurung (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This journal discusses the influence of social media as a realm of current developments on the electability of presidential and vice presidential candidates in general elections. Writing this journal uses the library study method, with data collection methods in the form of documentation. The analysis technique used is data analysis, through references from journals and books which are then analyzed by the author. The results obtained in this journal are that social media plays a major role in determining the electability of prospective presidential and vice presidential candidates in the general election. Social media is also a means of political communication and attracting the interest of the younger generation in determining their roles and interests in the presidential and vice presidential candidate pairs. However, sometimes social media itself backfires and backfires on presidential and vice presidential candidate pairs who cannot regulate the direction of their use of social media. In this case, negative things related to hoaxes, hate speech and misrepresentations can occur in social media forums. So it is important for every prospective partner to respond and use social media wisely because this has a big influence on their electability.